Clinical and radiographic evaluation of factors influencing the presence or absence of interproximal gingival papillae - Perez, Fabiano [UNESP]; Segalla, José Cláudio Martins [UNESP]; Ferreira, Paulo Martins; Lauris, José Roberto Pereira; Ribeiro, João Gustavo Rabelo [UNESP] (My University, 2012)
This study evaluated factors that may influence the presence or absence of interproximal papillae. Clinical evaluation consisted of visual determination, and quantitative analyses were made using millimeter grids on radiographs. Patients (n = 45) were divided into three groups according to age. Data were analyzed using the chi-square test followed by the Student t test (α = .05). The distance from the contact point to the bone crest had significant influence on papilla presence in both anterior and posterior sites (P < .05), whereas the width between roots of adjacent teeth did not. The papilla was missing more frequently in anterior sites. The presence of papillae was not agedependent. © 2012 by Quintessence Publishing Co Inc.